PERAN CAMAT DALAM PEMBINAAN PENYELENGGARAAN PEMERINTAHAN DESA DI DESA HARAPAN BARU KECAMATAN MANDAU KABUPATEN BENGKALIS TAHUN 2012 - Nicko Saputra; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The presence of disciplinary offenses committed village head, district head due to the lack of a role in fostering the delivery of Village Governance in the New Hope Village District of Saber Bengkalis district, sub-district which is not maximized direct supervision tasks village head, this happens due to lack of approach between the sub-district with the Village Head New Hope Village District of Saber Bengkalis, so Camats not get proper information about the implementation of the village chief task, whether it is carried out properly or not. This study aims to determine the role of sub-district in the implementation of the Government guidance in the village of New Hope Village District of Bengkalis Saber 2012. Methods used in the study using qualitative methods. Respondents of this study were sub-district, the District Secretary, Head of Government Affairs Village, Village Consultative Body, the village head, village secretary, Institute for Village Empowerment, Youth in the New Hope Village District of Saber number 8 respondents. Data were collected by conducting interviews and documentation. The results showed the district head coaching role of implementation of the Government in the village of New Hope Village New Hope Village District of Saber Bengkalis in 2012 through the conduct giving guidance, provision of guidance, mentoring, provision of training, supervision had a role, but there are still obstacles. In terms of fostering the organization of village government obstacles is the lack of human resources in rural and less budget execution guidance, but sub-district also received support in improving labor discipline that village officials with the high spirits of the apparatus in the village following the development activities undertaken and also the support of the village to the sub-district officials to always conduct development activities in order to improve the organization of village government work discipline in the village of New Hope.Keywords: Role of sub-district, Coaching, Organizing Village Government